Design and Implementation of Edible Plant Demonstration Gardens: A Case Study of the Putnam County Extension Edible Garden - Gail Hansen; Joe Sewards; Rebecca Almeida; Andrew Dunn (EDIS, 2012)
Demonstration gardens are a collection of plants assembled and organized in a manner that allows garden visitors to access and study them. Most gardens are designed with a particular focus and include plants that support the purpose and educational theme of the garden. This case study features an edible plant demonstration garden that was designed and installed in Hastings, Florida, on the Extension office grounds. The UF/IFAS program and the Partnership for Water, Agriculture, and Community Sustainability (FPWACS) designed and implemented the demonstration garden using a step-by-step process that is discussed in this 15-page fact sheet written by Gail Hansen, Joseph Sewards, Rebecca Almeida, and Andrew Dunn, and published by the UF Department of Environmental Horticulture, November 2012.